1. DINAMIKA KEMISKINAN DI ERA PEMERINTAHAN SUSILO BAMBANG YUDHOYONO – YUSUF KALLA. - Taufiq, Ahmad (FORUM, 2007)
Many policies has been implemented in poverty alleviation by SBY-Kalla Administration. The policy are not only implemented in various main programs, but also supported by big and significant budget. Unfortunately, from 2005-2006 periods there is a tendency of increasing poverty, from 15,97% (2005) to 17,75% (2006). The main reasons are those administration’s programs are based on invalid data, not supported by macro economic policy, charitative in nature, and politically-orinted.